The Effect of Multifaceted Intervention on Iron Intake and Hemoglobin (Hb) Levels in Teenage Girl with Mild Moderate Anemia at The Vocational School State of Tanjung Sari in South Lampung Regency - Catur Ariwibowo; Reni Zuraida; Susianti Susianti (Universitas Aisyah Pringsewu, 2022)
Introduction: The prevalence of anemia in teenage girls in Lampung Province is still quite high. In preventing and overcoming anemia in teenage girls, it is possible to increase the intake of iron-rich foods and supplementation with blood-added tablets (TTD). It is necessary to develop innovative multifaceted interventions in improving dietary intake behavior, especially iron. This study was conducted to analyze the effect of multifaceted intervention on iron intake and hemoglobin (Hb) levels in teenage girls with mild moderate anemia at the Vocational High School in Tanjung Sari, South Lampung Regency. Methodology: Quasy experimental research with one group pretest and posttest design. The study was conducted from January to May 2022 with a sampling technique that is consecutive sampling on anemic teenage girls at the vocational high school state in Tanjung Sari and the number of research samples was 41 respondents. The respondents carried out a multifaceted intervention in the form of nutrition education, food supervision for parents and teachers and the provision of iron supplementation for six weeks. The analysis test used paired t-test with the SPSS program and it was considered to have a significant effect if p0.05. Result: There was an increase in the average iron intake (increase 7.60 mg) and an increase in the average hemoglobin level (increase 1.06 g/dL). The results is showed a significant effect of multifaceted intervention on iron intake (p = 0.000) and a significant effect on hemoglobin (Hb) levels (p = 0.000). Discussion: Based on the results of the analysis showed that there was a significant effect of multifaceted intervention on iron intake and hemoglobin (Hb) levels in anemic teenage girls at the vocational high school in Tanjung Sari.